In vitro evaluation of microparticles with Laurus nobilis L. extract prepared by spray-drying for application in food and pharmaceutical products - Chaumun, M (2020)
Laurus nobilis L. is an aromatic evergreen tree, rich in phenolic compounds that grant it therapeutic properties (e.g. antioxidant, anti-inflammatory and antiviral). However, polyphenols are very sensitive to external conditions, being necessary to develop an adequate delivery system to protect these active ingredients, reducing their reactivity with external factors, and allowing their release at the right place and time. In this context, in this experimental work, the design of microparticles containing L. nobilis L. extract was studied, using the spray-drying as encapsulation technique and the modified chitosan, sodium alginate and arabic gum as encapsulating agents. At the end, the L. nobilis L. extract microparticles were characterized, and their effectiveness evaluated. The microparticles containing the L. nob ilis L. extract were obtained with product yields that ranged from 48.0% to 53.7%, and encapsulation efficiencies between 72.9% and 99.3%. These microparticles had a spherical morphology and, depending on the encapsulating agent used, could present a smooth or an irregular surface. The particles loaded with gallic acid had a total phenolic content that ranged from 540 to 560 mg GAE/L, while for the L. nob ilis L. particles this parameter ranged from 400 to 430 mgGAE/L. The microparticles size ranged from 1.3 to 3.2 Fast release patterns were observed in deionized water, being the core material released after 6 min when it is used arabic gum, and after 9 and 15 min for the modified chitosan and sodium alginate particles, respectively. The mathematical models that presented a better adjustment to the experimental release profiles and, consequently, had the higher correlation coefficients values, were the zero order, the Korsmeyer-Peppas and the Weibull equations. The Weibull model was the one that best fit to the experimental release profile, presenting correlation coefficients ranging from 0.992 to 0.999. In summary, the L. nobilis L. extract was successfully encapsulated, allowing its subsequent application into food and pharmaceutical products.